2014
DOI: 10.1080/17513758.2014.895433
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in virus infection dynamics models

Abstract: In this paper, on the basis of the simplified two-dimensional virus infection dynamics model, we propose two extended models that aim at incorporating the influence of activation-induced apoptosis which directly affects the population of uninfected cells. The theoretical analysis shows that increasing apoptosis plays a positive role in control of virus infection. However, after being included the third population of cytotoxic T lymphocytes immune response in HIV-infected patients, it shows that depending on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Our finding that disease outcome in experimental FIP infection is associated with the degree of lymphopenia is in agreement with a conclusion made by de Groot-Mijnes et al (2005), who studied experimental disease caused by the highly virulent type II FIPV-70-1146 -''Our combined observations suggest a model for FIP pathogenesis in which virus-induced T-cell depletion and the antiviral T-cell response are opposing forces and in which the efficacy of early T-cell responses critically determines the outcome of the infection.'' This conclusion has been mirrored by Fan et al (2014), who postulated that ''depending on intensity of the apoptosis of healthy cells, the apoptosis can either promote or comfort the long-term evolution of HIV infection.' ' We did not determine the lymphocyte subclasses that were most affected although the severity of the lymphocyte depletion suggested that both T and B subsets were involved.…”
Section: Discussionmentioning
confidence: 91%
“…Our finding that disease outcome in experimental FIP infection is associated with the degree of lymphopenia is in agreement with a conclusion made by de Groot-Mijnes et al (2005), who studied experimental disease caused by the highly virulent type II FIPV-70-1146 -''Our combined observations suggest a model for FIP pathogenesis in which virus-induced T-cell depletion and the antiviral T-cell response are opposing forces and in which the efficacy of early T-cell responses critically determines the outcome of the infection.'' This conclusion has been mirrored by Fan et al (2014), who postulated that ''depending on intensity of the apoptosis of healthy cells, the apoptosis can either promote or comfort the long-term evolution of HIV infection.' ' We did not determine the lymphocyte subclasses that were most affected although the severity of the lymphocyte depletion suggested that both T and B subsets were involved.…”
Section: Discussionmentioning
confidence: 91%
“…Guo and Ma [12] introduced a model based on Bystander apoptosis and studied its global behaviour. Fan et al [8] proposed a mathematical model which included the activation-induced apoptosis phenomenon and examined the effect of apoptosis on viral infection dynamics, with special emphasis on HIV.…”
Section: Introductionmentioning
confidence: 99%
“…HIV infects vital cells such as helper T cells, specifically CD4 + T cells, dendritic cells and macrophages in the human immune system [3]. The infection of HIV which can self-replicate leads to low levels of CD4 + T cells through a number of mechanisms, including apoptosis of uninfected bystander cells (see, e.g., [17,18,45]). The cellmediated immunity is easily inactivated, and the body becomes gradually very susceptible to opportunistic infections if CD4 + T cells fall below a critical level.…”
mentioning
confidence: 99%